Serum Cytokine Profile in Alzheimer's Disease Patients After Ingestion of an Antioxidant Beverage - Rubio-Perez, J.M.; Morillas-Ruiz, J.M. (CNS & Neurological Disorders - Drug Targets, 2013)
The major neuropathologic hallmarks in Alzheimer's disease (AD) consist of neuronal cell loss in selected brain regions, as well as deposition of extracellular senile plaques and intracellular neurofibrillary tangles. Further to these lesions, neuroinflammation is a feature of AD pathology and is thought to contribute to the neurodegeneration. Inflammation clearly occurs in pathologically vulnerable regions of the AD brain, with increased expression of acute phase proteins and pro-inflammatory cytokines. The healthy properties of green tea and apple are linked closely to their content of phenolic compounds. Although the beneficial effects of these compounds are clear, relatively few studies have focused on their anti-inflammatory effects in vivo. The aim of the present study was to test whether daily consumption of a beverage with high antioxidant power combining extracts of green tea and apple over a period of eight months would affect biomarkers of inflammation in AD patients in initial phase, moderate phase and a control group. Administration of the antioxidant beverage (AB) to the three groups did not produce a significant change in serum levels of the antiinflammatory cytokines interleukin-4 and interleukin-10. In contrast, AB decreased serum levels of the pro-inflammatory cytokines interleukin-2 (AD moderate phase vs control group at eight months), interferon-γ (control group vs AD moderate phase and AD initial phase vs placebo beverage at four months) and tumor necrosis factor-α (AD initial phase vs AD moderate phase at four months). AB was more effective against inflammation in the early period of AD, and could be used as a natural complementary therapy to alleviate or improve symptoms of inflammation in early stages of AD.
Keywords: antioxidant